Accuracy of Platelet Counting by Optical and Impedance Methods in Patients with Thrombocytopaenia and Microcytosis - Mohamed-Rachid Boulassel; Raya Al-Farsi; Sulaiman Al-Hashmi; Hamad Al-Riyami; Hammad Khan; Salam Al-Kindi (Sultan Qaboos University Medical Journal, 2015)
Objectives: Obtaining accurate platelet counts in microcytic blood samples is challenging, even with the most reliable automated haematology analysers. The CELL-DYN™ Sapphire (Abbott Laboratories, Chicago, Illinois, USA) analyser uses both optical density and electronic impedance methods for platelet counting. This study aimed to evaluate the accuracy of optical density and electrical impedance methods in determining true platelet counts in thrombocytopaenic samples with microcytosis as defined by low mean corpuscular volume (MCV) of red blood cells. Additionally, the impact of microcytosis on platelet count accuracy was evaluated. Methods: This study was carried out between February and December 2014 at the Haematology Laboratory of the Sultan Qaboos University Hospital in Muscat, Oman. Blood samples were collected and analysed from 189 patients with thrombocytopaenia and MCV values of <76 femtolitres. Platelet counts were tested using both optical and impedance methods. Stained peripheral blood films for each sample were then reviewed as a reference method to confirm platelet counts. Results: The platelet counts estimated by the impedance method were on average 30% higher than those estimated by the optical method (P <0.001). The estimated intraclass correlation coefficient was 0.52 (95% confidence interval: 0.41–0.62), indicating moderate reliability between the methods. The degree of agreement between methods ranged from -85.5 to 24.3 with an estimated bias of -30, suggesting that these methods generate different platelet results. Conclusion: The impedance method significantly overestimated platelet counts in microcytic and thrombocytopaenic blood samples. Further attention is therefore needed to improve the accuracy of platelet counts, particularly for patients with conditions associated with microcytosis.